A Systematic Literature Review on Bad Smells-5 W's: Which, When, What, Who, Where - Sobrinho, Elder Vicente de Paulo; De Lucia, Andrea; Maia, Marcelo de Almeida (IEEE transactions on software engineering, 2021)
Bad smells are sub-optimal code structures that may represent problems needing attention. We conduct an extensive literature review on bad smells relying on a large body of knowledge from 1990 to 2017. We show that some smells are much more studied in the literature than others, and also that some of them are intrinsically inter-related (which). We give a perspective on how the research has been driven across time (when). In particular, while the interest in duplicated code emerged before the reference publications by Fowler and Beck and by Brown et al., other types of bad smells only started to be studied after these seminal publications, with an increasing trend in the last decade. We analyzed aims, findings, and respective experimental settings, and observed that the variability of these elements may be responsible for some apparently contradictory findings on bad smells (what). Moreover, we could observe that, in general, papers tend to study different types of smells at once. However, only a small percentage of those papers actually investigate possible relations between the respective smells (co-studies), i.e., each smell tends to be studied in isolation. Despite of a few relations between some types of bad smells have been investigated, there are other possible relations for further investigation. We also report that authors have different levels of interest in the subject, some of them publishing sporadically and others continuously (who). We observed that scientific connections are ruled by a large "small world" connected graph among researchers and several small disconnected graphs. We also found that the communities studying duplicated code and other types of bad smells are largely separated. Finally, we observed that some venues are more likely to disseminate knowledge on Duplicate Code (which often is listed as a conference topic on its own), while others have a more balanced distribution among other smells (where). Finally, we provide a discussion on future directions for bad smell research.